Effect of Bacillus subtilis on mechanical and self-healing properties in mortar with different crack widths and curing conditions - Nattapong Yamasamit; Panisa Sangkeaw; Wittaya Jitchaijaroen; Chanachai Thongchom; Suraparb Keawsawasvong; Viroon Kamchoom‬ (Scientific Reports, 2023)
This research aimed to investigate the effectiveness of Bacillus subtilis (B. subtilis) in self-healing cracks in concrete and enhancing concrete strength through microbial induced calcium carbonate precipitation (MICP). The study evaluated the ability of the mortar to cover cracks within 28 days, taking into account the width of the crack, and observed the recovery of strength after self-healing. The use of microencapsulated endospores of B. subtilis was also examined for its impact on the strength of concrete. The compressive, splitting tensile, and flexural strengths of normal mortar were compared to those of biological mortar, and it was found that biological mortar had a higher strength capacity. Microstructure analysis using SEM and EDS showed that bacterial growth increased calcium production, contributing to the improved mechanical properties of the bio-mortar.
Keywords: Microbial Applications in Construction Materials; Marine Sponges and Natural Products; Synthetic Organic Chemistry Methods